CA19-9 as a non-invasive marker for disease activity in Hepatitis B patients: is there any role? - Nik Ahmad, Nik Nur Fatnoon; Hasmoni, Mohamed Hadzri; Jaafar, Khairul Azhar (2010)
The combined elevation of tumor markers carbohydrate antigen 19-9 (CA 19-9) and carbohydrate antigen 125 (CA 125) has been shown to be associated with the severity of liver fibrosis in patients with liver disease. We assessed the association between CA 19-9 and viral hepatitis B activity which will allow us to know the usefulness of CA 19-9 as a surrogate marker for the disease activity in hepatitis B patients. Methods: A prospective study involving 60 patients with hepatitis B surface antigen positive carrier was performed. These patients were divided into 2 groups according to HBeAg positivity. Tumor marker CA 19-9 was determined using routine laboratory methods and correlated with the disease activity by measuring hepatitis B viral DNA (HBV DNA) and serum alanine transaminase (ALT) and aspartate transaminase (AST) levels. Results: Eleven (18%) were HBeAg positive and 49 (82%) were HBeAg negative. The mean (standard deviation) age in the former group was 40.7 (11.7) years and in the latter group was 40.8 (12.5) years (p = 0.98). There was no significance difference between the two groups with respect to the levels of serum ALT/AST, HBV DNA and CA 19-9. There was no significant correlation seen between CA 19-9 and serum ALT/AST. It was the same with the levels of HBV DNA. Discussions and conclusion: The use of CA 19-9 as a non-invasive marker for disease activity in patients with hepatitis B infection was not useful. There was no role of CA 19-9 in hepatitis B patients to assess the disease activity.